Smart Tourism And Consumer Behavior Research: Mapping Global Trends Through A Bibliometric Lens (2018–2025) (International Journal of Scientific Research and Management (IJSRM), 2025)
Smart tourism has emerged as a strategic priority in both scholarship and practice, while consumer behavior has been reshaped profoundly by digital transformation. This study applies bibliometric analysis of 2018–2025 Scopus data to map intellectual structures, research trends, and thematic priorities in the field. The dataset was processed with Bibliometrix in R, Biblioshiny, and VOSviewer, generating visualizations including keyword co-occurrence networks, thematic maps, and three-fields plots. Findings confirm that research has shifted from early technological infrastructures, such as smartphones and ubiquitous computing, toward consumer-centered agendas emphasizing personalization, user experience, and artificial intelligence. At the same time, our analysis suggests a geographic reorientation, with China and India emerging as leading contributors alongside established European hubs. Thematic clusters highlight the integration of destination management, satisfaction, immersive technologies, and smart city perspectives, underscoring the hybrid nature of the field. Taken together, the study provides a comprehensive overview of smart tourism and consumer behavior research, clarifies existing gaps, and outlines pathways for integrating technological innovation with sustainable and human-centered development.